2020
DOI: 10.1002/pds.5033
|View full text |Cite
|
Sign up to set email alerts
|

Allopurinol‐induced severe cutaneous adverse drug reactions: Risk minimization measures in Malaysia

Abstract: Purpose To describe risk minimization measures (RMMs) implemented in Malaysia for allopurinol‐induced severe cutaneous adverse drug reactions (SCARs) and examine their impact using real‐world data on allopurinol usage and adverse drug reaction (ADR) reports associated with allopurinol. Methods Data on allopurinol ADR reports (2000‐2018) were extracted from the Malaysian ADR database. We identified RMMs implemented between 2000 and 2018 from the minutes of relevant meetings and the national pharmacovigilance ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…This may be due to the risk minimisation measures implemented in the early 2010s, namely the restriction of allopurinol initiation only to specialists in the public health sector, removal of uric acid as a routine blood test to prevent allopurinol initiation for asymptomatic hyperuricaemia and various awareness programmes such as reminder letters to prescribers on asymptomatic hyperuricaemia, publications in the Malaysian Adverse Drug Reaction Advisory Committee bulletin. 36 We found that the average incidence of allopurinol-induced SCAR in Malaysia over 5 years (2015-2019) was 2.5 cases in every 1000 new users. Our findings were consistent with a Taiwan study that reported an incidence rate of 3-4.68 per 1000 users.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…This may be due to the risk minimisation measures implemented in the early 2010s, namely the restriction of allopurinol initiation only to specialists in the public health sector, removal of uric acid as a routine blood test to prevent allopurinol initiation for asymptomatic hyperuricaemia and various awareness programmes such as reminder letters to prescribers on asymptomatic hyperuricaemia, publications in the Malaysian Adverse Drug Reaction Advisory Committee bulletin. 36 We found that the average incidence of allopurinol-induced SCAR in Malaysia over 5 years (2015-2019) was 2.5 cases in every 1000 new users. Our findings were consistent with a Taiwan study that reported an incidence rate of 3-4.68 per 1000 users.…”
Section: Discussionmentioning
confidence: 78%
“…However, for allopurinol‐induced SCARs, the majority of reports came from healthcare professionals as these severe cases usually required hospitalisation. We expect the under‐reporting rate would be low, as many awareness measures including ADR reporting for allopurinol have been carried out for this issue 36 . The findings of our study enabled us to address this challenge and determine the estimated incidence rate for allopurinol‐induced SCARs from drug utilisation data as a denominator.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…[13] Initially producing printed material solely targeting healthcare professionals, NPRA now utilizes electronic communication as well as social media, and disseminates information to consumers. [13] The quality of risk communication content may be enhanced through multidisciplinary collaboration, by inviting nonregulatory healthcare professionals and in the future, consumer group representatives or patients to contribute articles and commentaries. Involvement of different stakeholders with various perspectives would result in communication which appeals to a broader audience.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Various risk communication methods have been used in Malaysia over the past 30 years, including press releases, a national bulletin, safety alerts via email or social media, product package inserts, Direct Healthcare Professional Communication (DHPC) letters, and educational materials. However, our previous study [13] revealed that the risk communication methods, speci cally related to allopurinol, did not have a signi cant impact on ADR reporting and prescribing practice.…”
mentioning
confidence: 84%